2001
DOI: 10.1006/cyto.2001.0882
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of Two CXC Chemokines, Mip-2 and Kc, and Their Receptors

Abstract: CXC chemokines, macrophage inflammatory protein-2 (MIP-2) and KC, (a cloning designation based on ordinate and abscissa position) as well as the CXC chemokine receptor, CXCR2, are expressed in a variety of cells and tissues in adult mice. Targeted deletion of the gene encoding murine CXCR2 does not result in obvious changes in the development of the organ system of the mouse, though the CXCR2 −/− mouse is compromised with regard to its ability to resist infection, heal wounds, and maintain homeostasis when cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Indeed, studies in our laboratory revealed a rapid expression of KC and MIP-2 in the skin of mice infected with L. major (15). KC and MIP-2 are the functional homologues of IL-8 in mice (12).…”
Section: Vol 70 2002mentioning
confidence: 96%
“…Indeed, studies in our laboratory revealed a rapid expression of KC and MIP-2 in the skin of mice infected with L. major (15). KC and MIP-2 are the functional homologues of IL-8 in mice (12).…”
Section: Vol 70 2002mentioning
confidence: 96%
“…A sheep anti-murine Duffy polyclonal Ab was used at 1/50 dilution to immunolocalize Duffy Ag in WT lungs following total body irradiation. The verification of the murine Duffy Ab and method for Duffy immunostaining have been previously described (25). Amino-ethylcarbazole (red chromogen) was used as substrate for peroxidase.…”
Section: Murine Duffy Immunohistochemistrymentioning
confidence: 99%
“…We determined Duffy Ag expression in the lungs following total irradiation in WT mice using a murine Duffy-specific Ab (25). Immunoreactivity was present in the lung endothelium (Fig.…”
Section: Lethally Irradiated Mice Are Fully Reconstituted With Donor mentioning
confidence: 99%
“…DARC has been established as a promiscuous chemokine receptor that can bind several chemokines, including CXCL1, to which it binds with the highest affinity (27). The expression of KC (the mouse ortholog of human CXCL1) and DARC was found to follow parallel temporal patterns and tissue localization during mouse development (28), suggesting that a relationship may exist between the two. In general, DARC was found to maintain chemokine homeostasis in the blood (29) and to facilitate chemokine transcytosis and presentation across endothelium (30,31).…”
mentioning
confidence: 96%